PROFITABILITAS SEBAGAI DASAR PENILAIAN KINERJA KEUANGAN PADA KSP CREDIT UNION BAHTERA SEJAHTERA KEWAPANTE - Lusia Trivania Pereira; Andreas Rengga; Imelda Virgula Wisang (Jurnal Projemen UNIPA, 2026)
Savings and Loan Cooperatives (KSP) play a strategic role as microfinance institutions that promote members' financial welfare through savings and loan services based on trust and togetherness. This study aims to analyze profitability as the basis for financial performance assessment of KSP Credit Union Bahtera Sejahtera Kewapante during the 2023–2025 period. The analysis focuses on three main profitability ratios—Return on Equity (ROE), Profit Margin (PM), and Assets Turnover (AT)—along with interpretation of performance trends, causal factors of fluctuations, and their implications for the cooperative's operational sustainability. The research employs a descriptive quantitative approach with data collection techniques through direct observation, documentation of financial statements for the last three years, and financial ratio analysis. Results indicate a significant decline in profitability performance: ROE decreased from 2.01% (2023) to -0.91% (2024) and slightly improved to -0.25% (2025); Profit Margin fell from 13.81% to -7.75% and -2.24%; while Assets Turnover showed a downward trend from 0.049 times to 0.039 times in 2025. All ratios remain far below ideal standards (ROE ≥10%, PM ≥20%, AT ≥1 time), indicating inefficiency in capital management, insufficient income to cover operational expenses, and low asset productivity. These conditions are caused by declining business income, rising operational costs, and weakening member economic activity. The findings confirm the critical need for optimizing productive loan disbursement, enhancing operational cost efficiency, and increasing active member participation as essential strategies to restore profitability and ensure the long-term sustainability of the cooperative.